On being a Professional Medical Witness (Res Medica, 2014)
When asked by the Editor to contribute an article on this topic, I became conscious of the fact that as a result of my arthritic leg which has defied the best efforts of clinical colleagues to heal, my recent Court appearances have been few and far between. Perhaps this means that I can take a relatively detached view of the Court rather than one dominated by current attacks of hyper-adrenalinism.I doubt if there are many people called to give professional medical evidence who approach the witness box without some quickening of the heartbeat. So if it happens to you, you can at least feel you are in good company. But it is the essence of a good witness that he is free of emotion, and this state depends firstly upon experience, and secondly on one's preparation of material before the trial.